Monitoring corrosion-induced thickness loss of stainless steel plates using the electromechanical impedance technique. (25th November 2020) - Liu, Yang; Feng, Xin
Abstract: Stainless steel plates are widely used in steel structures. Corrosion damage of a stainless steel plate can induce the thickness and mass loss of the stainless steel plate. The corrosion-induced thickness loss (CITL) is one of the main reasons for the degradation of the stiffness and bearing capacity of the stainless steel plate, which endangers the safety of the structure and causes economic losses. Therefore, effective monitoring of the CITL of the stainless steel plate can help to ensure the safety of steel structures. In this study, a novel monitoring method for the CITL of the stainless steel plate based on the electromechanical impedance (EMI) technique is presented. The effective mechanical admittance (EMA) of a simply supported thin stainless steel plate under the excitation of a single surface-bonded piezoelectric transducer is derived theoretically; the resonance frequency shift ( Δ f ) of the bending vibration mode in the admittance signature is extracted as the CITL-sensitive feature to identify the CITL of the stainless steel plate. The quantitative relationship between Δ f and CITL, based on the EMA, is established theoretically for monitoring the CITL of the stainless steel plate. The effectiveness of the proposed method is verified by experiments. The experimental results demonstrate that the proposed method can sensitively identify, accurately quantify and predict the CITL of the stainless steel plate, and has excellent stability and reliability. This method can not only overcome the limitation of the existing statistics-based EMI methods that cannot quantify the CITL, but also compensate for the weakness of commonly-used non-destructive testing methods that cannot quantitatively predict CITL in an on-line monitoring manner. The proposed method provides an effective monitoring and tracking tool for the CITL of the stainless steel plate.